African American men significantly underestimate their risk of having prostate cancer at the time of biopsy. Issue 2 (16th November 2011) - Hemmerich, Joshua A.; Ahmad, Faraz S.; Meltzer, David O.; Dale, William
Abstract Background Guidelines for prostate cancer (PCa) screening recommend physicians to have an informational discussion with patients. At the time of biopsy, patients should be informed of their heightened PCa risk, particularly African Americans (AA) who have significantly higher diagnostic and mortality risk. We tested predictors of patients' estimation of their likelihood of having PCa at the time of biopsy. Methods A convenience sample of AA (n = 207) and white (n = 271) biopsy patients was surveyed at the time of prostate biopsy. Participants gave likelihood estimations of having PCa and data on their socio‐demographics, health, clinical status, and general and PCa‐specific anxiety. Binary logistic regressions tested for predictors of the patients' estimations and biopsy results. Results Fifty‐one percent of AA men answered that they had a '0%' likelihood of having PCa versus 19% of whites, whereas 57% of AA men had abnormal biopsies compared with 42% of whites. In logistic regressions, predictors of patient answers of 0% chance of PCa were AA ethnicity (OR = 4.50; p < 0.001), lower cancer‐specific anxiety (OR = 0.93; p < 0.01), less education (OR = 2.38; p < 0.05), and less urinary disturbance (OR = 0.70; p < .05). In a second regression, AA patients trended towards higher positive biopsy rates (OR = 1.43; p = 0.17). Conclusions At biopsy, AA more often estimated their likelihood of PCa as 0%, despite higher risks. Reasons for these low estimates and their potential contribution to poor treatment outcomes of AA patients require further investigation. Copyright © 2011 John Wiley & Sons, Ltd.